2017
DOI: 10.1111/jocn.13912
|View full text |Cite
|
Sign up to set email alerts
|

The nurse's role in palliative care: A qualitative meta‐synthesis

Abstract: Aims and objectives: To explore how nurses, across various health systems, describe their role in providing palliative care for patients with life-threatening illnesses.Background: Despite the fact that nurses make up the largest group of healthcare

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
140
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 41 publications
(220 reference statements)
2
140
1
11
Order By: Relevance
“…This role can be explained as that of a servant leader (who builds and serves a community; Greenleaf, ) in LTC settings. When providing palliative care in hospitals and home care, nurses—as the health professionals who spend the most time with such people—ensure their availability and coordinate care (Sekse, Hunskar, & Ellingsen, ). However, in the LTC settings examined in this study, nurses were not the health professionals who were closest to residents.…”
Section: Discussionmentioning
confidence: 99%
“…This role can be explained as that of a servant leader (who builds and serves a community; Greenleaf, ) in LTC settings. When providing palliative care in hospitals and home care, nurses—as the health professionals who spend the most time with such people—ensure their availability and coordinate care (Sekse, Hunskar, & Ellingsen, ). However, in the LTC settings examined in this study, nurses were not the health professionals who were closest to residents.…”
Section: Discussionmentioning
confidence: 99%
“…Advocating on behalf of residents (Dahlin, ) was found to be particularly important for nurses in LTC settings, where most residents' cognitive function is declining. This advocacy role is consistent with EOL care in other settings (Karbasi et al, ; Sekse et al, ). However, nurses also mentioned that the dignity of dying residents was disturbed by unnecessary treatment to keep them alive as per relatives' wishes but contrary to the residents' own.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses were reflective on their practice but experienced contextual barriers including lack of space, time, and educational preparation for providing high‐quality EOL care. Sekse, Hunskar, and Ellingsen () did a qualitative meta‐synthesis of nurses' role in palliative care across health services and found that nurses' valued roles included “being available” to provide and coordinate care, for which they need knowledge and training, guidance, and support. Nurses' role for EOL care in LTC settings will and should differ from that in hospital and homecare settings along with differences of context including residents' length of stay, purpose of admission, physician placement, or nurse‐resident/nurse‐patient ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses play vital roles in caring for patients during their end‐of‐life process. Nurses contribute expertise in palliative care and symptom management across a wide variety of practice settings, and they provide emotional, mental and psychological support to those navigating life‐limiting illness and death (Sekse, Hunskår, & Ellingsen, ). A lack of clarity in the professional contributions that registered nurses are permitted to make during a MAiD process can potentially disrupt and disconnect nurses during this complex and emotionally charged time.…”
Section: Political Ramifications and Professional Tensionsmentioning
confidence: 99%
“…Nurses play vital roles in caring for patients during their end-of-life process. Nurses contribute expertise in palliative care and symptom management across a wide variety of practice settings, and they provide emotional, mental and psychological support to those navigating life-limiting illness and death (Sekse, Hunskår, & Ellingsen, 2018).…”
Section: Professional Considerationsmentioning
confidence: 99%